Hydrobiological and Behavioral Parameters of Fresh Clarias gariepinus Exposed to Dichlorvos Concentrations - Usifoh, Cyril O.; Effiong, Anietie P.; Etim, Emmanuel I.; Udobre, Aniefiok S.; Usifoh, Stella F. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The use of dichlorvos (organometallic pesticide) in public health and agriculture to control pests has led to the accumulation of dichlorvos residues in the aquatic environment. The objective is to establish the potential diagnostic tools (hydrobiological and behavioural parameters) in assessing the lethal and sublethal effects of dichlorvos on fish. Cultured Clarias gariepinus were sourced from two fish farms in Uyo metropolis, Akwa Ibom State, Nigeria. All cultured samples for acute toxicological studies were fortified with 2%, 5%, 10%, 20% dichlorvos and exposed for 24, 48, 72, 96 h, and above 96 h intervals respectively while 2%, 5% concentrations of dichlorvos at the same periods of exposure were used for chronic studies. Dichlorvos residues were present in all cultured fresh post-fingerlings exposed to the pesticide. This revealed significant different variations (p<0.05) and positive correlation in behaviour, mortality rate, survival rate, weight loss of Clarias gariepinus treated with dichlorvos concentrations as well as changes in pond water quality (hydrobiological) parameters ranging from temperature, pH to dissolved oxygen. Dichlorvos, therefore, constituted a major constraint to hydrobiological and behavioural cycles of fresh fish and aquacultures under study, and these parameters can be useful biomarkers in environmental bio-monitoring of pesticides contamination.